Towards an ideal antiretroviral regimen for the global HIV epidemic - Beatriz Grinsztejn; Lara E. Coelho; Paula M. Luz; Valdilea G. Veloso (Elsevier, 2017)
Currently, immediate initiation of antiretroviral therapy (ART) is recommended for all individuals with HIV infection. However, among the 37 million people estimated to be living with HIV/AIDS, only 17 million are actively on treatment. Optimal use of ART among HIV-infected and at-risk individuals reduces morbidity, mortality, transmission and acquisition of HIV infection. ART regimen choices are affected by factors such as economic differences between resource-rich and low- and middle-income countries (LIMC), drug availability, and considerations for use in special populations. Ideal ART regimens combine high efficacy, high tolerability, low toxicity, low pill burden, affordability and global availability. Here, we highlight five aspects to be considered when thinking of an ideal global ART regimen: (1) the co-administration with other medications especially tuberculosis treatment; (2) treatment for specific populations such as women, children, adolescents, older people and acutely infected individuals; (3) efficacy; (4) safety, tolerability and convenience; and (5) affordability and global access for all PLWH.